2018
DOI: 10.1016/j.bbr.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural brain abnormalities and associated behavioral changes in mice after low-intensity blast exposure

Abstract: Explosive blast-induced mild traumatic brain injury (mTBI), a "signature wound" of recent military conflicts, commonly affects service members. While past blast injury studies have provided insights into TBI with moderate- to high-intensity explosions, the impact of primary low-intensity blast (LIB)-mediated pathobiology on neurological deficits requires further investigation. Our prior considerations of blast physics predicted ultrastructural injuries at nanoscale levels. Here, we provide quantitative data us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 47 publications
5
67
1
Order By: Relevance
“…In another recent blast TBI mouse model, Konan et al observed decreased synapse density within the cortex, which mirror our results indicating a reduction in the dendritic arbor within the cortex 41 . In a previous study using the same blast TBI mouse model, myelinated axonal damage and mitochondrial abnormalities were also observed 42 . These morphological changes were also accompanied by deficits in neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…In another recent blast TBI mouse model, Konan et al observed decreased synapse density within the cortex, which mirror our results indicating a reduction in the dendritic arbor within the cortex 41 . In a previous study using the same blast TBI mouse model, myelinated axonal damage and mitochondrial abnormalities were also observed 42 . These morphological changes were also accompanied by deficits in neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…In the context of low level exposure without a direct impact to the head, this study indicated that median levels of serum Nf-L and tau were elevated (although tau did not meet statistical thresholds). Exposure is reported to impact brain tissues in a way that may mirror a sub-concussive event [24,25], causing cytoskeletal abnormalities and demyelination in rodent models [26][27][28]. In animal models, serum tau is elevated within 6h-1d of and the heavy chain isoform of neurofilament is increased within 2h after mild exposure [29].…”
Section: A Subset Of Tbi-related Proteins Are Potential Biomarkers Ofmentioning
confidence: 99%
“…Nevertheless, experimental manipulation of peak pressure in mice and rats has revealed that even low levels induce neuronal loss, white matter alterations, cell signaling disruptions, and behavioral changes ( 18 20 ). Moreover, ultrastructural brain changes, poorer motor and memory performance, as well as increased anxiety levels, have been observed in mice exposed to primary low-intensity blast in the absence of head motion ( 21 ).…”
Section: Introductionmentioning
confidence: 99%